PRECEDENTS OF SOLUTION AND COURT OF JUSTICE OF EUROPEAN UNION - Gołba, Filip (Review of European and Comparative Law, 2020)
Article elaborates on how Court of Justice of European Union treats its precedential rulings. Its principal purpose is to examine the distinction between precedent of solution and precedent of interpretation and assess whether the distinction may serve the purpose of reconciliation of Court of Justice’s heavy reliance on precedent with reluctance toward recognising precedent as a formal source of law manifested by civil law lawyers. According to some scholars, Court of Justice’s precedents are merely precedents of interpretation, therefore they are not instance of judge-made law. Herein, it is argued, that the distinction is insufficient to prove their conviction is right.